Investimento estrangeiro direto, inovação regional e capacidade de absorção no Brasil - Cassânego, Vitor Melão (2023)
Foreign direct investment (FDI) has been seen by the literature as an influential factor in the technological evolution of host-countries innovation ecosystems, with several developing nations such as Brazil aiming to attract FDI as a way to potentialize their development through innovative output. However, the evidence on whether FDI configures a source of positive or negative influence on regional innovation capabilities is definitely mixed. Furthermore, despite the existence of studies regarding emerging economies, there is a gap when it comes to the regional level in Brazil. We intend to contribute to the literature by examining whether regional MNEs are inducing high or low-intensity innovations in this last context. Thus, this study aims to complement academic investigations by analyzing the influence of multinational enterprises (MNEs) on regional innovation intensity in Brazil in the state of São Paulo using a unique regional-level FDI database in a panel ranging from 2010 to 2016. The results indicate that the presence of MNEs boosts the production of high and low-intensity inventions, slightly more for the latter than the former. In other words, FDI is better for the production of inventions in general, which can later become innovation, but even more so for utility models and certificates of addition. These findings corroborate with various regression specifications and alternative estimation methods explored throughout the academic literature while remaining robust to endogeneity issues.